JSEGC 2021
DOI: 10.20517/jsegc.2021.06
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria planning of microgrids for rural electrification

Abstract: Aim:The objective of this study is to facilitate decision makers' selection of groups of components for isolated microgrid which should not only be economically attractive and efficient but also acceptable from various aspects. The microgrid is designed to serve a rural remote region of Tanzania with an approximate energy demand of 1000 kWh/day. Methods: A comprehensive comparison has been presented using (Hybrid Optimization Model for Electric Renewable) HOMER Pro software and fuzzy analytic hierarchy process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This can be achieved through different aggregation methods, such as weighted sum, weighted product, or outranking methods like the technique for order of preference by similarity to the ideal solution (TOPSIS) or the preference ranking organization method for enrichment evaluation (PROMETHEE). The result is a ranking or scoring of the alternatives based on their overall performance [31].…”
Section: Multi-criteria Decision Making (Mcdm)mentioning
confidence: 99%
“…This can be achieved through different aggregation methods, such as weighted sum, weighted product, or outranking methods like the technique for order of preference by similarity to the ideal solution (TOPSIS) or the preference ranking organization method for enrichment evaluation (PROMETHEE). The result is a ranking or scoring of the alternatives based on their overall performance [31].…”
Section: Multi-criteria Decision Making (Mcdm)mentioning
confidence: 99%
“…The authors found that the CC strategy outperforms the LF strategy based on the economic aspect. The research in [26] investigated multicriterion planning of a PV/wind/micro-hydro/biogas/battery HES to cover the electricity demand in a rural area in Tanzania using the LF strategy. The results indicated that the suggested HES is an interesting solution to electrify the selected site.…”
Section: Introductionmentioning
confidence: 99%
“…According to the inventors, the CC method outperforms the LF method from a financial standpoint. The investigation in [24] a PV/wind/miniature hydro/biogas/battery HES was explored using the LF approach multicriteria arranging to meet the demand for energy in a rural Tanzanian location. The results demonstrated that the proposed HES is an innovative method for billing the chosen location.…”
Section: Introductionmentioning
confidence: 99%